GIJZELING; METODE PENYELESAIAN KREDIT MACET HUKUM PERDATA - Subaidi Subaidi (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2016)
Bad Creditisa problem loan or a non-performing loanthat for some reasons a customer reneging on promises to pay off debts after due dateso there is a delay or not paid altogether so that arose a bad credit or a bad debt.The existence of bank can not be separated from risk in the banking world. So it is necessary to minimize them by keeping the quality of loans in a case of nonperforming loans.Gijzeling is an effort to press the case of a bad credit which is the act to a physical or an agency of a debtor by entering them into prisonso that they loses the right to freedom.This act is expected to be a deterrent effect, because they feel uncomfortable with any restriction in action, so that the debtor decide to immediately pay or pay off that debts